On the taxonomy of two poorly known species of Geosesarma De Man, 1892 (Crustacea: Brachyura: Sesarmidae) from the Philippines - Ng, Peter K. L.; Lemaitre, Rafael (Zootaxa, 2017)
The identities of two poorly-known species of semiterrestrial crabs of the genus Geosesarma De Man, 1892, from the Philippines, are clarified. The types of Sesarma (Sesarma) vicentense Rathbun, 1914 (from Luzon), and Sesarma (Geosesarma) rathbunae Serène, 1968 (from Panay), are examined and both species are rediagnosed with detailed figures. Comparisons with allied congeners are also provided.